Sustainable development and the degree of implementation of European Union environmental directives - Bąk, Iwona; Wawrzyniak, Katarzyna; Sulikowski, Piotr (Frontiers in Environmental Science, 2024)
EU Member States must implement environmental policy in accordance with the specified rules, including standards supporting the implementation of the adopted EU policies. The standards (target values) for the levels of environmental indicators are included in EU directives. Compliance with EU environmental standards is already bringing many benefits, but there is still much to be done. The aim of our study is to assess the current levels of environmental indicators in EU countries, since prompt achievement of their target values is a prerequisite for sustainable development in this area. A classical correspondence analysis was used to evaluate the degree of differentiation of the levels of indicators in the EU countries based on the data presented in a binary matrix of indicators. As a result, countries have been identified in which indicators monitoring the state of environmental protection have achieved a level in line with the target values indicated in EU directives, and those in which this level has not been achieved. The research procedure used in the article is universal in the sense that it can be used to assess the situation of the objects under study (countries, regions) regardless of the specifics of the phenomenon under study, provided that comparable data are available.